Economic and environmental efficiency of fertilizers use for enhance the fertility of degraded soils in the Republic of Moldova - Tamara Leah; Nicolai Leah (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
In recent decades, high fertility of soils in the Republic of Moldova are subjected to more intensive accelerated degradation due to anthropogenic activity. Situation created causing further intensive development of land desertification processes and leads to worsening of the ecological situation in the country. There are currently affected by degradation processes of different intensity 56.4 percent of agricultural land. One measure provides for local sources of organic fertilizers, along with the minerals. Agronomic, economic and ecological efficiency of fertilizers use in the agriculture of Moldova found that application of fertilizers has positive effects on soil fertility along with other measures to restore degraded soils.
Keywords: 330; economic efficiency; organic fertilizers; degraded soils; soil fertility